(3UhQI ELGRI dGHf gdGd ef GdTjN Ydi Hf YeGO GdOjf GdMfais - (3Ydj Hf YeGO GdOjf GdMfajs ((3eOQSI GdcdGSI TeGdi (B_ (3GdLGeY GdCehi(B_ (3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ TeS GdOjf GdMfjai hcGf eef LO ai GddMGb GdTjN CHh GdaVGFd TeS GdOjf eMeO gdGd GdMfai bO dGRefi eOi WhjdI hMVQ Edi ai OQhS LdjdI s
(3BNQgG (B:s
(3hdfG HGdeSGfjO WQb CNQi ZjQ eG ai gPG GdLGeY eHjfI HGdagQSJ hbO JMQQ GfJgGA eG PcQ ef GdbQGAI hGdCPf hGdELGRI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HChdgG fbhd eNJdaIs
(3JGQjNs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdeLGejYs